Upaya Mempertahankan Eksistensi Baju Thrift Sebagai Budaya Populer Di Bengkulu - Putri , Intan Dwi (Universitas Dehasen Bengkulu, 2024)
People has different interest about fashion trend issue. Fashion is a how ro syled up your style and make up which what becoming a trend right now, fashion is an attribute that we as a human, wearing it to define who we are specifically as a different person with the others and from what different social group from the others. Society in general have a different buy capacityone with the others to reach what fashion attribute they want to buy., surely people has a different taste and need. Thrift store is one of the choise that people needed, the market segmentation, quality that they offer is not different from new fashion attributes that sell in department store in general. A secondhand clothes right now is not just about commodity that we just underestimated, but it has a different value for their devotee. This research is for knowing how lifestyle in young generation for having a good looking with fashion trends right now. Life style in feberal is a something that connected with trend fashion and from social media like blogger, website fashion and zine. This research is doing with interview with the informant that has been choose by researcher. Researcher also doing this with direct observation into local traders in Pasar Panorama, thrift store, and second hand clothes consumer. The theory that has been use in this research is life style theory from Chaney that represent human habbits that never desire to do.